The Research Comparison Between the Consonants of Bahasa Indonesia and Chinese Mandarin - Clarosa Amanda Hasel (Mandarinable: Journal of Chinese Studies, 2022)
Indonesian Students face a lot of difficulties when learning Chinese Mandarin, it is very common that them to mispronounce the consonants of Chinese Mandarin. There are not a lot of Indonesian Students who can pronounce Chinese Mandarin consonants accurately. Phonetics teaching is a very important part of learning other languages.   Bahasa Indonesia is classified as “The Family of Austronesian Language”, and Chinese Mandarin is classified as Sino-Tibetan Language System. Although they have a different language systems, the two languages have a lot of similarities and differences in every aspect of it. If we look at the consonants of Bahasa Indonesia and Chinese Mandarin, Bahasa Indonesia has 23 consonants, and Chinese Mandarin has 22 consonants. These 2 kinds of languages have similarities and different points of the pronunciation and pronunciation methods.